The theory of the Collatz process and the method of dynamical balls : The theory of the Collatz process - Agama, Theophilus (My University, 2022)
In this paper we introduce and develop the theory of the Collatz process and the method of dynamical balls. We leverage this theory to study the Collatz conjecture. This theory also has a subtle connection with the infamous problem of the distribution of Sophie germain primes. We also provide several formulation of the Collatz conjecture in this language. Furthermore, we introduce and develop the notion of dynamical systems induced by a fixed a ∈ N and their associated induced dynamical balls. We develop tools to study problems requiring to determine the convergence of certain sequences generated by iterating on a fixed integer.
Keywords: Collatz; index; order; backward Collatz process